Simultaneous measurement of curvature and strain based on fiber Bragg grating in two-dimensional waveguide array fiber - Wu, Zhifang (2014)
We report on the fabrication of a fiber Bragg grating (FBG) with multiple resonances in a two-dimensional waveguide array microstructured optical fiber containing 91 cores. Theoretical investigation reveals that these resonances originate from the identical and nonidentical mode couplings between forward-propagating and backward-propagating LP0m-like (m=1, 2, 3; LP refers to linearly polarized) supermodes. Since both the central wavelength and minimum transmission of these resonant dips respond differently to curvature and axial strain, this FBG can be applied in the simultaneous measurement of curvature and axial strain.